AL-SAYYID MUHAMMAD IBNU 'ALAWĪ AL-MĀLIKĪ WA KHASHĀISHU MANHAJIHI AL-FIQHIY: السيد محمد بن علوي المالكي وخصائص منهجه الفقهي - Ahmad Azaim Ibrahimy; Muhammad Amanullah; Muntaha Artalim Zaim (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
This research unveils the characteristics of the jurisprudential approach of Sayyid Muhammad al-Maliki, who is one of the prominent Maliki scholars of this era. The researcher found that the characteristics of his jurisprudential approach are represented in three points: First: Opening the door to ijtihad, because the rulings in the Qur’an and Sunnah are limited. Second: Considering the interest, and by inducting partial texts and their rulings, reasons and rulings, he reached a general matter that represents a result for it. Third: His general jurisprudence of human rights because the principles of Islamic jurisprudence are a general system for human society.